6ER-016 Economic value of unused high cost experimental infusion drugs: a potential saving for the national health system. (24th March 2020) - Borchetto, SL; Taddei, B; Marchesi, F; Nozza, S; Gregis, F; Gatti, V; Rossi, L
Abstract : Background and importance: Antineoplastic and immune-modulatory drugs are top for public pharmaceutical spending. About half of the clinical trials conducted in Italy concern oncohaematology, with an important investment by big pharma and a source of savings for the national health system (NHS). According to GCPs and the regulation (EU) N. 536/2014, pharmacists are involved in traceability, storage, return and destruction of investigational medicinal products to ensure their quality, the safety of the subjects involved, and the reliability and robustness of the data. Aim and objectives: To quantify the economic value of unused infusion drugs at our centre. Material and methods: To guarantee the traceability system, we used a database for all of the main information regarding the drug (product description, batch number, expiry date, location, storage condition) and its accountability (status change date, received, used, available, kit, subject ID, shipment/cycle/returned/destroyed). The analysed data were collected from January 2018 to October 2019 for the clinical trials managed by the oncology and haematology departments. An economic value (ex-factory price) was assigned to the high cost drugs destroyed on-site or returned to the sponsor. We considered 5 days up to the effective expiry date to create a useful range for their potential use. Results: Twenty-six drugs were destroyed on-site and 69 returned to the sponsor from 4 compassionate use programmes, 11 non-profit clinical trials and 34 profit clinical trials: in 55.8% of cases the drugs had not expired (€2.3 million). In 5 of 21 cases (23.8%) the non-expired drugs had been destroyed or returned in the non-profit clinical trials compared with 46 of 70 cases (65.7%) in the profit clinical trials. The economic value of the high cost drugs on the market was about €4.1 million (64.2% oncological, 35.8% haematological drugs), which is about 29% of the total annual value of €14.5 million for infusion drugs managed by our pharmacy. Conclusion and relevance: Based on our data, the drug supply process needs to be improved and greater collaboration is needed (between AIFA–sponsor–clinical trial centres–CRO) to reduce the waste described and optimise the available economic resources. References and/or acknowledgements: https://www.ema.europa.eu/en/documents/scientific-guideline/ich-e-6-r2-guideline-good-clinical-practice-step-5_en.pdf https://ec.europa.eu/health/sites/health/files/files/eudralex/vol-1/reg_2014_536/reg_2014_536_en.pdf No conflict of interest.